(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2022)
Transitional marine systems are affected by the interaction of wave, tidal and fluvial processes, with different impacts on salinity, turbidity, energy and depositional rate. Benthic organisms are influenced by these processes, and so, the ichnological signatures of these deposits represent key elements for environmental analysis. The Lajas Formation (Middle Jurassic, Neuquén Basin Argentina) is characterized by deposits accumulated in shallow transitional marine environments, mainly deltaic systems. A detailed study of sedimentological and ichnological features of the Lajas Formation developed on subsurface core samples allows to reconstruct the depositional conditions and evolution of unit and determine that the prevalent processes on the reworking of the sediments is fluvial, with subordinated wave processes. Fourteen sedimentary facies were defined, grouped into five facies associations: interdistributary plain, distributary channels, fairweather and storm-generated waves bars, delta front mouth bars, and prodelta. The ichnological analysis allows to differentiate 21 trace fossils: representing 5 ichnofacies: Skolithos (Mararonichnus suite), Skolithos (or Rosellia), impoverished Cruziana, Cruziana, Scoyenia and Zoophycos. Two surfaces with Glossifungites suites were recognized, and they are interpreted in two different ways, one related to authigenic changes and the other as a surface of stratigraphic importance, related to the variation in sea level. Finally, the whole section studied constitutes a prograding fluvio-dominated deltaic system, representing a Highstand System Tract, with minor transgressive events.